2005
DOI: 10.1002/pmic.200401264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fatty acid binding proteins as markers associated with the initiation and/or progression of renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) representing the most common neoplasia of the kidney in Western countries is a histologic diverse disease with an often unpredictable course. The prognosis of RCC is worsened with the onset of metastasis, and the therapies currently available are of limited success for the treatment of metastatic RCC. Although gene expression analyses and other methods are promising tools clarifying and standardizing the pathological classification of RCC, novel innovative molecular markers for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 43 publications
2
41
1
1
Order By: Relevance
“…Of these, 24 proteins have been described previously [16][17][18] and almost all of the presently obtained results were consistent with the earlier observations. For instance, our finding of higher levels of proteins involved in glycolysis (such as glyceraldehyde-3-phosphate dehydrogenase and fructose-bisphosphate aldolase A) was consistent with earlier reports [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…Of these, 24 proteins have been described previously [16][17][18] and almost all of the presently obtained results were consistent with the earlier observations. For instance, our finding of higher levels of proteins involved in glycolysis (such as glyceraldehyde-3-phosphate dehydrogenase and fructose-bisphosphate aldolase A) was consistent with earlier reports [16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 93%
“…Five selected chimeric transcript predictions were confirmed in DLBCL cell lines and we conducted further analysis of one particular chimera, namely LTR2-FABP7, which we confirmed encodes a novel isoform of the FABP7 protein with an alternative first coding exon. FABP7 is normally expressed in brain, but not in blood, and is up-regulated in various solid tumor types, where it is a marker for poor prognosis (28)(29)(30)(31). However, it has not been associated with DLBCL or any other lymphoma before this report.…”
mentioning
confidence: 74%
“…Although FABP7 expression has not been linked with blood cancers before, up-regulation has been reported in various solid cancer types, including malignant glioma (28), melanoma (31), renal cell carcinoma (30), and aggressive triple negative breast cancer (47) and is associated with poor prognosis and also increased cell growth in vitro (48). To assess the requirement for chimeric FABP7 in DLBCL proliferation and cell-cycle progression in vitro, DLBCL cell lines were nucleofected to express three independent RNAi sequences targeting FABP7 and a nonsilencing scrambled control sequence.…”
Section: Activation Of Te-gene Chimeras Is Associated With Epigeneticmentioning
confidence: 99%
“…previous studies revealed that B-FABp was overexpressed in renal cell carcinoma tissues (7,12,13). the present study proves that B-FABP influences the proliferation and migration in renal cell carcinoma cell lines whereas the invasion ability of the cells did not depend on their B-FABp content.…”
Section: Discussionmentioning
confidence: 89%